Monolithic film manufacturing method, monolithic film, display device manufacturing method, and display device
The laser peeling technology forms an anisotropic conductive film monolithic film of a predetermined shape and transfers it to the wiring substrate or the electrode surface of the light emitting element, which solves the problem of residual conductive film hindering light transmission and poor single-chip transferability in the prior art, and realizes efficient LED display manufacturing.
Patent Information
- Application Number
- CN202380062541.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-13
- Filing Date
- 2023-08-02
- Publication Date
- 2025-04-08
AI Technical Summary
Prior Art When manufacturing sub-mm LED and micro LED displays, the process method of using ACF bonding LEDs causes bonding resin and conductive particles to remain between the LED spacing, hindering the transmission of light, and the poor shape of the monolithic chip leads to deterioration of transferability and increasing manufacturing time.
By irradiating laser light on the anisotropic conductive film provided on the substrate from the side of the substrate, the conductive film of the irradiated portion is removed, and a single piece of a predetermined shape is formed on the substrate, the single piece is transferred to the electrode surface of the wiring substrate or the light emitting element, and the light emitting element is mounted through the single piece.
It realizes excellent processing and transferability of a single piece, improves beat time, ensures high light transmittance of the light emitting element and the production efficiency of the display.
Smart Images

Figure CN119790718A_ABST
Abstract
Description
Technical Field
[0001] The present technology relates to a method for manufacturing a monolithic film and a monolithic film for monolithicizing connecting films such as anisotropic conductive film (ACF: Anisotropic Conductive Film) and adhesive film (NCF: Non Conductive Film). In addition, it relates to a method for manufacturing a display device and a display device in which light-emitting elements are connected and arranged via a monolithic film. In particular, it relates to a method for manufacturing a display device and a display device in which LED elements such as sub-millimeter LEDs (Light Emitting Diodes: light-emitting diodes) and micro LEDs are connected and arranged. This application claims priority based on Japanese patent application No. 2022-145317 filed in Japan on September 13, 2022, which is incorporated into this application by reference. Background Art
[0002] As the next generation of displays, the development of sub-millimeter LED and micro-LED displays has attracted attention. Sub-millimeter LED and micro-LED displays are constructed by arranging tiny light-emitting elements on a substrate, so the backlight required for liquid crystal displays can be omitted, thereby achieving thinner displays, and further wide color gamut, high definition, and power saving.
[0003] Patent document 1 discloses a process for bonding LEDs with ACF. In the process described in Patent document 1, since the entire ACF is adhered to the component mounting surface of the substrate, the adhesive resin and conductive particles of the ACF remain between the pitches of each LED. Therefore, when light transmittance is required for the light-emitting element array, the transmission of light is hindered and excellent light transmittance cannot be obtained. In addition, when the film is provided on the entire surface of the substrate, there is a concern that repair work will be required when a defect occurs, which will increase the impact on productivity.
[0004] On the other hand, when the ACF is attached only directly below the LED, the adhesive resin and conductive particles of the ACF will not remain between the LED pitches and will not hinder the transmission of light, thereby achieving light transmittance.
[0005] However, it is difficult to stick a connection film such as ACF only directly below the LED. For example, when a connection film sheet is formed and then stuck to a substrate, if the shape of the sheet is poor, the transferability of the sheet to the substrate or LED will deteriorate, and the takt time of display manufacturing will deteriorate.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: U.S. Patent Application Publication No. 2015 / 0255505 Summary of the invention
[0009] Problems to be solved by the invention
[0010] The present technology has been proposed in view of such conventional actual conditions, and provides a method for manufacturing a monolithic film and a monolithic film capable of obtaining excellent processability of a monolithic film, and a method for manufacturing a display device and a display device.
[0011] Solutions for solving problems
[0012] The manufacturing method of the monolithic film of the present technology is as follows: an anisotropic conductive film provided on a substrate is irradiated with laser from the substrate side, the anisotropic conductive film of the irradiated portion is removed, and a monolithic film of a specified shape composed of the anisotropic conductive film is formed on the substrate, the thickness of the anisotropic conductive film is greater than 0.9 times and less than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C is greater than 2000 Pa·s and less than 800000 Pa·s.
[0013] The monolithic film of the present technology has a monolithic film of a specified shape composed of an anisotropic conductive film, the thickness of the anisotropic conductive film is greater than 0.9 times and less than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C is greater than 2000 Pa·s and less than 800000 Pa·s.
[0014] The manufacturing method of the display device of the present technology comprises: a forming step, irradiating an anisotropic conductive film provided on a substrate with a laser from the substrate side, removing the anisotropic conductive film of the irradiated portion, and forming a single piece of a specified shape composed of the anisotropic conductive film on the substrate; a transfer step, transferring the single piece of the specified shape to a specified position of a wiring substrate or an electrode surface of a light-emitting element; and a mounting step, mounting the light-emitting element on the wiring substrate via the transferred single piece, the thickness of the anisotropic conductive film being not less than 0.9 times and not more than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C being not less than 2000 Pa·s and not more than 800000 Pa·s.
[0015] The manufacturing method of the connection structure of the present technology comprises: a forming step, irradiating an anisotropic conductive film provided on a substrate with a laser from the substrate side, removing the anisotropic conductive film of the irradiated portion, and forming a single piece of a specified shape composed of the anisotropic conductive film on the substrate; a transfer step, transferring the single piece of the specified shape to a specified position of a first electronic component; and a mounting step, mounting a second electronic component on the wiring substrate via the transferred single piece, the thickness of the anisotropic conductive film being not less than 0.9 times and not more than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C being not less than 2000 Pa·s and not more than 800000 Pa·s.
[0016] The display device of the present technology comprises: a plurality of light-emitting elements; a wiring substrate for arranging the light-emitting elements; and a cured film for connecting the plurality of light-emitting elements to the wiring substrate, wherein the cured film is formed by curing a single piece of a predetermined shape composed of an anisotropic conductive film, the thickness of the anisotropic conductive film is greater than 0.9 times and less than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C is greater than 2000 Pa·s and less than 800000 Pa·s.
[0017] The connection structure of the present technology comprises: a first electronic component; a second electronic component; and a cured film, which connects the first electronic component and the second electronic component, wherein the cured film is formed by curing a single piece of a predetermined shape composed of an anisotropic conductive film, the thickness of the anisotropic conductive film is greater than 0.9 times and less than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C is greater than 2000 Pa·s and less than 800000 Pa·s.
[0018] Effects of the Invention
[0019] According to this technology, excellent processability of a single piece can be obtained, and the takt time can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a cross-sectional view schematically showing an anisotropic conductive film, Figure 1 (A) indicates that 90% or more of the conductive particles are present at the reference value, and the reference value is close to the substrate side. Figure 1 (B) indicates that 90% or more of the conductive particles are present at the reference value, and the reference value is close to the opposite side of the substrate. Figure 1 (C) shows a state where the conductive particles are dispersed in the thickness direction.
[0021] Figure 2 This is a diagram schematically showing an example of a laser lift-off device according to the present embodiment.
[0022] Figure 3 is a diagram for explaining an example of a method for manufacturing a single-sheet film shown as Specific Example 1, Figure 3 (A) represents an anisotropic conductive film substrate having an anisotropic conductive film formed on a base material, Figure 3 (B) represents the case where the removal portion is peeled off in the first direction, Figure 3 (C) represents the case where the removal portion is peeled off in the second direction, Figure 3 (D) represents a single film in which an anisotropic conductive film is formed on a substrate.
[0023] Figure 4 (B) is a diagram schematically showing an example of irradiation with laser light passing through an opening of a mask.
[0024] Figure 5 (A) is a microscope photograph showing an example of a wafer in which burrs are generated during wafer processing. Figure 5 (B) is a microscope photograph showing an example of a single sheet in which curling and defect occurred during single sheet transfer.
[0025] Figure 6 (A) is a diagram schematically showing an example of a mask having a light shielding portion in an opening window portion. Figure 6 (B) is a diagram schematically showing an example of irradiation with laser light passing through an opening of a mask.
[0026] Figure 7 This is a diagram schematically showing an example of a mask having a plurality of light shielding portions in an opening window portion.
[0027] Figure 8 is a diagram schematically showing an example of the shape of the opening of the mask, Figure 8 (A) represents a mask having a rectangular light shielding portion in the opening window portion, Figure 8 (B) represents a mask having a square light shielding portion in the opening window portion, Figure 8 (C) represents a mask having a rounded rectangular light shielding portion in the opening window portion, Figure 8 (D) shows a mask having a circular light shielding portion in the opening window portion.
[0028] Fig. 9 It is a cross-sectional view schematically showing an anisotropic conductive film provided on a substrate.
[0029] Fig.10 It is a cross-sectional view schematically showing a state where the individual film and the wiring substrate are opposed to each other.
[0030] Fig.11This is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred to a predetermined position on a wiring board and arranged by irradiating a laser beam from the substrate side.
[0031] Fig.12 It is a cross-sectional view schematically showing a state where light emitting elements are mounted on a chip arranged at a predetermined position on a wiring substrate.
[0032] Fig.13 This is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred to an electrode position on a wiring board and arranged by irradiating laser light from the substrate side.
[0033] Fig.14 It is a cross-sectional view schematically showing a state where a light emitting element is mounted on a chip arranged in electrode units of a wiring substrate.
[0034] Fig.16 It is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film provided on a base material and light-emitting elements arranged on a transfer substrate are opposed to each other.
[0035] Fig.16 This is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred onto light-emitting elements arranged on a transfer substrate by irradiating a laser beam from the substrate side.
[0036] Fig.17 This is a cross-sectional view schematically showing a state in which the light emitting element to which the individual pieces have been transferred is further transferred onto a wiring substrate.
[0037] Fig.18 is a diagram schematically showing a method for manufacturing a mounting body, Fig.18 (A) indicates the process of preparing a single piece. Fig.18 (B) represents the process of transferring the single piece to the substrate, Fig.18 (C) represents the process of temporarily fixing the μLED element. Fig.18 (D) shows the process of crimping the μLED element.
[0038] Fig.19 It is a top view schematically showing an evaluation substrate used for a lighting test.
[0039] Fig. 20 (A) is a top view schematically showing an electrode surface of a μLED element. Fig. 20 (B) is a diagram schematically showing a state where a μLED element is mounted on an evaluation substrate. DETAILED DESCRIPTION
[0040] Hereinafter, embodiments of the present technology will be described in detail in the following order with reference to the drawings.
[0041] 1. Method for manufacturing a monolithic membrane
[0042] 2. Monolithic membrane
[0043] 3. Method for manufacturing display device
[0044] 4. Display device
[0045] 5. Examples
[0046] <1. Method for producing a single-sheet film>
[0047] The method for manufacturing a single film of this embodiment is to irradiate an anisotropic conductive film provided on a substrate with laser light from the substrate side, remove the irradiated portion of the anisotropic conductive film, and form a single film of a predetermined shape composed of the anisotropic conductive film on the substrate. Here, by setting the thickness of the anisotropic conductive film and the melt viscosity of the anisotropic conductive film at 30° C. to the following ranges, excellent processability of the single film can be obtained.
[0048] The thickness of the anisotropic conductive film is preferably 0.9 times or more and 8 times or less of the particle size of the conductive particles in the anisotropic conductive film, preferably 1 times or more and 7 times or less of the particle size of the conductive particles in the anisotropic conductive film, and more preferably 1.5 times or more and 5 times or less of the particle size of the conductive particles in the anisotropic conductive film. In addition, the thickness of the anisotropic conductive film is preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 6 μm or less, and more preferably 2 μm or more and 4 μm or less. By setting the thickness of the anisotropic conductive film to the above range, it is easy to tear due to laser irradiation, and a single piece shaped like a mask can be obtained. The thickness of the anisotropic conductive film can be measured using a known micrometer or a digital thickness gauge. For example, more than 10 locations can be measured and the thickness can be calculated by averaging.
[0049] The melt viscosity of the anisotropic conductive film at 30°C is preferably 2000 Pa·s or more and 800000 Pa·s or less, more preferably 5000 Pa·s or more and 500000 Pa·s or less, and further preferably 10000 Pa·s or more and 300000 Pa·s or less. If the viscosity is too low, the monolithic film will shrink after laser irradiation, and it will be difficult to maintain the monolithic film as a film. If the viscosity is too high, the film properties of the anisotropic conductive film are strong and it is difficult to remove it by laser irradiation. The melt viscosity of the anisotropic conductive film at 30°C can be measured using a rheometer, for example, by setting the measurement frequency to 10 Hz.
[0050] In addition, for the conductive particles in the anisotropic conductive film, it is preferred that more than 90% of the average value of the center position of the conductive particles in the thickness direction of the anisotropic conductive film be present, more preferably more than 92% of the average value of the center position of the conductive particles in the thickness direction of the anisotropic conductive film, and further preferably more than 95% of the average value of the center position of the conductive particles in the thickness direction of the anisotropic conductive film. Thus, the unevenness in the degree of ablation is suppressed, and a single piece with a shape like the shape of a mask can be obtained. The existence ratio of the conductive particles relative to the average value of the center position of the conductive particles in the thickness direction of the anisotropic conductive film can be calculated by observing the cross section of the anisotropic conductive film with a microscope and measuring the conductive particles. For example, a cross section of a specified range in which more than 200 conductive particles exist in the cross section of the anisotropic conductive film is used as a measurement object, and the center position of the conductive particles of the cross section of the measurement object is measured, and its average value is set as a reference value (reference line), and the proportion of conductive particles in which a part of the outer diameter of the conductive particles within the specified range touches the reference value (the shortest distance between the reference line and the end of the conductive particle is less than 0.5 times the particle size) is obtained. Here, the reference line is considered to be substantially parallel to the line of the film surface at the film cross section. In other words, the center position of the conductive particles in the thickness direction is the existence ratio of the conductive particles relative to the reference line in a predetermined range.
[0051] Figure 1 is a cross-sectional view schematically showing an anisotropic conductive film, Figure 1 (A) indicates that 90% or more of the conductive particles are present at the reference value, and the reference value is close to the substrate side. Figure 1 (B) indicates that 90% or more of the conductive particles are present at the reference value, and the reference value is close to the opposite side of the substrate. Figure 1 (C) shows a state where the conductive particles are dispersed in the thickness direction.
[0052] like Figure 1 (A)~ Figure 1 As shown in (C), anisotropic conductive films 2A to 2C are provided on substrate 1. The substrate 1 may be any substrate as long as it is transmissive to laser light, and preferably is made of quartz glass having high light transmittance over all wavelengths.
[0053] like Figure 1 (A) and Figure 1 As shown in (B), the anisotropic conductive films 2A and 2B preferably have 90% or more of the conductive particles 3 present at the reference value (reference lines L1 and L2). This can suppress the generation of burrs, defects, shrinkage, and elongation, and obtain a single piece with a shape similar to that of a mask. On the other hand, Figure 1As shown in (C), in the case of an anisotropic conductive film 2C in which the conductive particles 3 are dispersed in the thickness direction and the conductive particles 3 present in the reference value (reference line L3) are less than 90%, the degree of ablation becomes uneven when peeling is performed by laser irradiation, and it is sometimes difficult to obtain a single piece with a shape like the shape of the mask.
[0054] [Anisotropic conductive film]
[0055] The adhesive of the anisotropic conductive film is not particularly limited as long as it is an adhesive that is cured by energy such as heat or light, and can be appropriately selected from, for example, thermosetting adhesives, photocuring adhesives, and thermo-photocuring adhesives.
[0056] As thermosetting adhesives, for example, there are: thermo-anionic polymerization resin compositions containing epoxy compounds and thermo-anionic polymerization initiators, thermo-cationic polymerization resin compositions containing epoxy compounds and thermo-cationic polymerization initiators, thermo-radical polymerization resin compositions containing (meth)acrylate compounds and thermo-radical polymerization initiators, etc. As photocurable adhesives, for example, there are: photo-cationic polymerization resin compositions containing epoxy compounds and photo-cationic polymerization initiators, photo-radical polymerization resin compositions containing (meth)acrylate compounds and photo-radical polymerization initiators, etc. As heat-light curing adhesives, there are mixtures of thermosetting adhesives and photocurable adhesives, etc. It should be noted that (meth)acrylate compounds mean that both acrylic monomers (oligomers) and methacrylic monomers (oligomers) are included.
[0057] (Thermal cationic polymerization resin composition)
[0058] Hereinafter, as a specific example of the thermosetting adhesive, a thermal cationic polymerization type resin composition including a film-forming resin, an epoxy compound, and a thermal cationic polymerization initiator will be described as an example.
[0059] As a film-forming resin, for example, a high molecular weight resin having an average molecular weight of 10,000 or more is used. From the viewpoint of film formation, an average molecular weight of about 10,000 to 80,000 is preferred. As a film-forming resin, various resins such as butyral resin, phenoxy resin, polyester resin, polyurethane resin, polyester urethane resin, acrylic resin, polyimide resin, etc. can be listed. They can be used alone or in combination of two or more. Among them, butyral resin is preferably used from the viewpoints of film formation state, connection reliability, etc. The content of the film-forming resin is preferably 20 to 70 parts by mass, more preferably 30 to 60 parts by mass or less, and further preferably 45 to 55 parts by mass relative to 100 parts by mass of the thermosetting adhesive.
[0060] The epoxy compound is not particularly limited as long as it has one or more epoxy groups in the molecule, and may be, for example, a bisphenol A epoxy resin, a bisphenol F epoxy resin, or a urethane-modified epoxy resin. Among them, hydrogenated bisphenol A glycidyl ether may be preferably used. As a specific example of hydrogenated bisphenol A glycidyl ether, for example, the trade name "YX8000" manufactured by Mitsubishi Chemical Co., Ltd. may be cited. The content of the epoxy compound is preferably 30 to 60 parts by mass, more preferably 35 to 55 parts by mass or less, and further preferably 35 to 45 parts by mass, relative to 100 parts by mass of the thermosetting adhesive.
[0061] As a thermal cationic polymerization initiator, a thermal cationic polymerization initiator known as a thermal cationic polymerization initiator of an epoxy compound can be used, for example, an initiator that utilizes heat to generate an acid that can cause a cationic polymerization compound to undergo cationic polymerization, and known iodonium salts, sulfonium salts, phosphonium salts, ferrocenes, etc. can be used. Among them, it is preferred to use an aromatic sulfonium salt that exhibits good latency to temperature. As a specific example of an aromatic sulfonium salt-based polymerization initiator, for example, the trade name "SI-60L" manufactured by Sanshin Chemical Industry Co., Ltd. can be cited. The content of the thermal cationic polymerization initiator is preferably 1 to 20 parts by mass, more preferably 5 to 15 parts by mass or less, and further preferably 8 to 12 parts by mass relative to 100 parts by mass of the thermosetting adhesive.
[0062] It should be noted that other additives that may be added to the thermosetting adhesive include, as required, rubber components, inorganic fillers, silane coupling agents, diluent monomers, fillers, softeners, colorants, flame retardants, thixotropic agents, and the like.
[0063] The rubber component is not particularly limited as long as it is an elastomer with high cushioning properties (impact absorption), and specific examples thereof include acrylic rubber, silicone rubber, butadiene rubber, polyurethane resin (polyurethane elastomer), etc. As inorganic fillers, silicon dioxide, talc, titanium oxide, calcium carbonate, magnesium oxide, etc. can be used. The inorganic filler can be used alone or in combination of two or more.
[0064] By including a thermosetting adhesive having such a structure, the curing reaction during the formation of the individual pieces by laser can be suppressed, and the heat can be used to cure the individual pieces more quickly during the thermocompression bonding.
[0065] (Conductive particles)
[0066] As the conductive particles, known conductive particles for anisotropic conductive films can be appropriately selected and used. For example, metal particles such as nickel (melting point 1455°C), copper (melting point 1085°C), silver (melting point 961.8°C), gold (melting point 1064°C), palladium (melting point 1555°C), tin (melting point 231.9°C), nickel boride (melting point 1230°C), ruthenium (melting point 2334°C), and solder as a tin alloy can be listed. In addition, for example, metal-coated metal particles obtained by coating the surface of metal particles with metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, and ruthenium can be listed. In addition, for example, metal-coated resin particles obtained by coating the surface of resin particles such as polymers containing at least one monomer selected from polyamide, polybenzoguanamine, styrene, and divinylbenzene as monomer units with metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, and ruthenium can be listed. In addition, for example, metal-coated inorganic particles obtained by coating the surfaces of inorganic particles such as silicon dioxide, aluminum oxide, barium titanate, zirconium oxide, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and aluminum silicate glass with metals such as nickel, copper, silver, gold, palladium, tin, nickel boride, and ruthenium can be cited. In addition, the coating metal layer of the metal-coated resin particles and the metal-coated inorganic particles may be a single layer or a multilayer of different metals.
[0067] In addition, the conductive particles can also be subjected to an insulating coating treatment, for example, by coating them with insulating particles such as a resin layer, resin particles, and inorganic particles. It should be noted that the particle size of the conductive particles does not include the portion that has been subjected to the insulating coating treatment. The particle size of the conductive particles can be appropriately changed according to the area of the installed optical element, the electrode of the wiring substrate, the bump, etc., and is preferably 1 to 30 μm, more preferably 1 to 10 μm, and particularly preferably 1 to 3 μm. For example, in the case of installing micro-LED elements, the area of the electrodes and bumps is small, so the particle size of the conductive particles is preferably 1 to 3 μm, more preferably 1 to 2.5 μm, and particularly preferably 1 to 2.2 μm. The particle size can be measured by microscopic observation (optical microscope, metal microscope, electron microscope, etc.) for more than 200 particles, and the average value is taken.
[0068] In addition, in the case where the conductive particles are the metal-coated resin particles or metal-coated inorganic particles obtained by coating the metal on the resin particles or inorganic particles, the coating thickness of the metal is preferably 0.005 μm or more, more preferably 0.01 μm or more, preferably 10 μm or less, more preferably 1 μm or less, and further preferably 0.3 μm or less. The coating thickness is the thickness of the entire metal coating when the metal is coated with multiple layers. If the coating thickness of the metal is above the above lower limit and below the above upper limit, sufficient conductivity can be easily obtained, and the conductive particles will not be too hard, and it is easy to give full play to the characteristics of the above-mentioned resin particles and inorganic particles.
[0069] The coating thickness of the metal can be measured, for example, by observing the cross section of the conductive particle using a transmission electron microscope (TEM). With regard to the coating thickness, it is preferred that the average value of the coating thickness at any five locations be calculated as the coating thickness of one conductive particle, and it is more preferred that the average value of the thickness of the entire coating portion be calculated as the coating thickness of one conductive particle. The coating thickness is preferably obtained by calculating the average value of the coating thickness of each conductive particle for any ten conductive particles.
[0070] In addition, the shape of the conductive particles may include spherical, ellipsoidal, peaked, irregular, etc. Among them, spherical conductive particles are preferred because they are easy to control particle size and particle size distribution. In addition, the conductive particles may have protrusions on the surface in order to improve connectivity.
[0071] The anisotropic conductive film preferably has conductive particles arranged in an orderly manner in the surface direction. By orderly arranging the conductive particles in the surface direction, the particle surface density is uniform, and the conductivity and insulation can be improved. As the state in which the conductive particles are arranged in an orderly manner in the surface direction, for example, a plane lattice pattern having one or more arrangement axes of conductive particles arranged in a prescribed direction at a prescribed interval can be listed, and the plane lattice pattern can be listed as: rhombus lattice, hexagonal lattice, square lattice, rectangular lattice, parallel body lattice, etc. The conductive particles are arranged in an orderly manner in the surface direction, and in other words, the conductive particles are arranged in a top view of the film. In addition, the arrangement of the surface direction of the conductive particles can be random, or there can be a plurality of regions with different plane lattice patterns.
[0072] The particle surface density of the anisotropic conductive film can be appropriately designed according to the size of the electrode to be connected, and the lower limit of the particle surface density can be set to 500 particles / mm 2 Above, 20000 pieces / mm 2 Above, 40000 pieces / mm 2 Above, 50000 pieces / mm 2 The upper limit of the particle surface density can be set to 1500000 particles / mm 2 Below, 1,000,000 pieces / mm 2 Below, 500,000 pieces / mm 2 Below, 100,000 pieces / mm 2 As a result, even when the electrode size of the connection object is small, excellent conductivity and insulation can be obtained. The particle surface density of the anisotropic conductive film is the surface density of the arrangement part of the conductive particles when the film is formed during manufacturing. In the case of obtaining the particle number density based on multiple monoliths, the particle surface density can be obtained based on the area obtained by removing the space between the monoliths from the area including the monoliths and the space and the number of particles.
[0073] By making the anisotropic conductive film into a film shape, it is easy to set the anisotropic conductive film on the substrate. From the viewpoint of operability, a release film such as a polyethylene terephthalate film can be set on one or both sides of the anisotropic conductive film. In addition, the anisotropic conductive film can be laminated with an adhesive layer or a binder layer that does not contain conductive particles, and the number of layers and the laminated surface of the anisotropic conductive film can be appropriately selected according to the object and purpose.
[0074] Examples of methods for producing an anisotropic conductive film include a method of applying a solution of an anisotropic conductive adhesive on a substrate and drying the solution; and a method of forming an adhesive layer containing no conductive particles on a substrate and fixing the conductive particles to the resulting adhesive layer.
[0075] [Laser lift-off device]
[0076] As a device for forming a single piece of a predetermined shape by irradiation with laser, for example, a laser lift-off (LLO: Laser Lift Off) device can be used. The laser lift-off device irradiates a material layer formed on a substrate with laser light to peel the material layer from the substrate. Examples of laser lift-off devices include the product name "InvisiLUM-XTR" manufactured by Shin-Etsu Chemical Co., Ltd.
[0077] Figure 2 FIG. 1 is a diagram schematically showing an example of a laser lift-off device according to the present embodiment. Figure 2 As shown, the laser lift-off device 10 includes: a laser scanner 11 for scanning the optical axis of the laser; a mask 12 having a plurality of openings of a predetermined shape arranged at a predetermined pitch; a projection lens 13 for reducing and projecting the laser onto a donor substrate; a donor stage for holding the donor substrate; and an acceptor stage for holding the acceptor substrate. In the formation of the single film, an anisotropic conductive film substrate 20 obtained by forming an anisotropic conductive film 22 on a substrate 21 is held on the donor stage as a donor substrate, and a removal portion 23 of the anisotropic conductive film separated from the anisotropic conductive film substrate 20 is received by the acceptor substrate.
[0078] As the laser device, for example, an excimer laser that oscillates a laser with a wavelength of 180 nm to 360 nm can be used. The oscillation wavelength of the excimer laser is, for example, 193 nm, 248 nm, 308 nm, and 351 nm, and can be appropriately selected from these oscillation wavelengths according to the light absorptivity of the material of the anisotropic conductive film 22. In addition, when a release member is provided between the substrate 21 and the anisotropic conductive film 22, it can be appropriately selected according to the light absorptivity of the material of the release member.
[0079] The laser scanner 11 has a scanning mirror composed of a biaxial galvano scanner, for example, and scans the optical axis of the laser in the X-axis direction and the Y-axis direction toward the opening in the mask 12 and controls the pulse irradiation of the laser.
[0080] The mask 12 is formed with a pattern of windows of a predetermined size arranged at a predetermined pitch so that the laser irradiation on the interface between the substrate 21 and the anisotropic conductive film 22 has a predetermined shape. In the mask, the pattern is applied by, for example, chrome plating, and the window portion where the chrome plating is not applied transmits the laser, while the portion where the chrome plating is applied blocks the laser.
[0081] The projection lens 13 projects the laser light having passed through the pattern of the mask 12 onto the donor substrate. The donor stage has a moving mechanism that moves at least in the X-axis and the Y-axis, and moves the irradiation position of the donor substrate with the laser light.
[0082] The laser lift-off device 10 constitutes a scanning type reduction projection optical system, which includes: a laser scanner 11; a mask 12; a field lens arranged between the laser scanner 11 and the mask 12; and a reduction projection lens 13, at least the image side of which is telecentric.
[0083] The emitted light from the laser device is incident on the telescope optical system and transmitted to the laser scanner 11 in front of it. The laser light incident on the laser scanner 11 is adjusted by the telescope optical system to be substantially parallel light at any position within the moving range of the X-axis and Y-axis of the donor stage, so that it is incident on the laser scanner 11 with substantially the same size and the same angle (perpendicular).
[0084] The laser light that has passed through the laser scanner 11 is incident on the mask 12 via the field lens, and the laser light that has passed through the pattern of the mask 12 is incident on the projection lens 13. The laser light emitted from the projection lens 13 is incident on the substrate 21 side, and is accurately projected in the shape of the opening of the mask 12 at a predetermined position on the boundary surface between the substrate 21 and the anisotropic conductive film 22.
[0085] The pulse energy of the laser for imaging the interface between the substrate 21 and the anisotropic conductive film 22 is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and even more preferably 0.1 to 1 J. The fluence is preferably 0.001 to 2 J / cm 2 , more preferably 0.01 to 1 J / cm 2 , more preferably 0.05 to 0.5 J / cm 2 The pulse width (irradiation time) is preferably 0.01 to 1×10 9 Picoseconds, more preferably 0.1 to 1×10 7Picoseconds, more preferably 1 to 1×10 5 The pulse frequency is preferably 0.1 to 10,000 Hz, more preferably 1 to 1,000 Hz, and even more preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.
[0086] By using such a laser lift-off device, a shock wave is generated at the interface between the substrate 21 and the anisotropic conductive film 22, and the removed portion 23 of the anisotropic conductive film 22 is peeled off from the substrate 21, and a single piece of a predetermined shape can be formed with high precision and efficiency using the remaining portion on the substrate 21, and excellent processability can be obtained. In addition, the single piece of the predetermined shape is less affected by the irradiation of the laser, so the reaction rate of the single piece can be set to 25% or less, preferably 20% or less, and more preferably 15% or less, and excellent transferability can be obtained.
[0087] It should be noted that the reaction rate of the curable resin film before laser irradiation and the single piece obtained after laser irradiation can be determined by, for example, the reduction rate of the reactive group using FT-IR. In the case of a small single piece, the reaction rate can be measured from the end of the film obtained by punching the single piece. In addition, the reaction rate of the single piece before laser irradiation is preferably measured within 8 hours after being taken out of a cold storage and at room temperature, and the reaction rate of the single piece after laser irradiation is preferably measured within 8 hours after laser irradiation at room temperature.
[0088] In the case of a curable resin film using the reaction of an epoxy compound, for example, a sample can be prepared as follows and the reaction rate can be measured using FT-IR. First, a pencil-shaped cutter with a sharp tip is used to sample the cured single piece. Next, the sampled single piece is placed on a diamond anvil, made thin and flat on the diamond anvil, assembled on a sample holder, and installed on the device body.
[0089] It should be noted that the diamond anvil used in this measurement is a group of two pieces, and the sample is clamped between the two anvils for tightening and flattening. Then, a piece of anvil with the sample is used for measurement. The amount of sample required for measurement is extremely small. If the sample amount is too much, the sample cannot be flattened thinly, so the sample is measured in a state where the film thickness is thicker. As a result, the baseline is lowered or tilted, or the peak is saturated, and it is difficult to analyze the spectrum. Therefore, with regard to the sample amount, it is preferred to sample an amount that can be adjusted to a thin degree on the diamond anvil (for example, an amount that can be flattened to a film thickness of less than 10 μm).
[0090] The detector sensitivity is greatly improved by cooling, and the detector is cooled using liquid nitrogen for about 30 minutes before measurement. In addition, the measurement conditions of FT-IR are set as follows, for example.
[0091] Measurement method: transmission.
[0092] Measurement temperature: 25℃.
[0093] Measured humidity: below 60%.
[0094] Measurement time: 12 sec.
[0095] Detector spectral range: 4000~700cm -1 .
[0096] Then, the diamond anvil is mounted on the infrared microscope to perform background measurement. By making the background measurement position as close as possible to the sample measurement position, a good baseline can be easily obtained. Next, infrared rays are irradiated on the sample to obtain an IR spectrum. The methyl group (2930 cm -1 Nearby) and epoxy (914cm -1 The reaction rate can be calculated from the peak height of the epoxy group relative to the peak height of the methyl group before and after the reaction (for example, before and after laser irradiation) as shown in the following formula.
[0097] Reaction rate (%) = {1 - (a / b) / (A / B)} × 100
[0098] In the above formula, A is the peak height of the epoxy group before the reaction, B is the peak height of the methyl group before the reaction, a is the peak height of the epoxy group after the reaction, and b is the peak height of the methyl group after the reaction. It should be noted that when the peak of the epoxy group overlaps with other peaks, the peak height of the fully cured sample (reaction rate 100%) can be set to 0%.
[0099] In the case of a curable resin film using a reaction of a (meth)acrylate compound, similarly to epoxy compounds, for example, the methyl group (2930 cm -1 Nearby) and (meth)acryloyl (1635cm -1 The reaction rate can be calculated from the ratio of the peak height of the (meth)acryloyl group to the peak height of the methyl group before and after the reaction.
[0100] In addition, when the peak height of the (meth)acryloyl group is small, or when it has an alicyclic epoxy group or an oxetane group, for example, a sample can be prepared as follows, and the reaction rate can be determined by HPLC (High Performance Liquid Chromatography). First, use a pencil-shaped knife with a sharp tip to sample the cured single piece. Next, select a sample weighing more than 0.015 mg, then put it into a vial and add acetonitrile as an extraction solvent. The amount of extraction solvent is calculated by determining an arbitrary concentration within the range of 0.025-0.25%. Furthermore, the vial is installed in the main body of the measuring device, and HPLC measurement is performed, for example, under the following measurement conditions.
[0101] Extraction: ACN 0.025-0.25%.
[0102] Equipment: UPLC (manufactured by Waters).
[0103] Gradient conditions: A60B40 (hold for 1 min) → A1B99 after 5 min (hold for 6 min).
[0104] ※A is water / acetonitrile = 9:1, B is acetonitrile.
[0105] Flow rate: 0.4mL / min.
[0106] Chromatographic column: 10cm.
[0107] Measurement temperature: 40℃.
[0108] Injection volume: 5μL.
[0109] The reaction rate of a single piece can be calculated from the chromatogram obtained by HPLC by the decay rate of the reactive component before and after the reaction (before and after laser irradiation) as shown in the following formula.
[0110] Reaction rate (%) = {1-c / C} × 100
[0111] In the above formula, C is the peak height or peak area of the reactive component before the reaction, and c is the peak height or peak area of the reactive component after the reaction.
[0112] [Specific example 1]
[0113] The method for manufacturing the monolithic film shown as Specific Example 1 is as follows: using a mask having a quadrilateral opening window, an unnecessary portion of the anisotropic conductive film is peeled off from the substrate, and a quadrilateral monolithic film is formed from the remaining portion of the anisotropic conductive film.
[0114] Figure 3 is a diagram for explaining an example of a method for manufacturing a single-sheet film shown as Specific Example 1, Figure 3 (A) represents an anisotropic conductive film substrate having an anisotropic conductive film formed on a base material, Figure 3 (B) represents the case where the removal portion is peeled off in the first direction, Figure 3 (C) represents the case where the removal portion is peeled off in the second direction, Figure 3 (D) represents a single film having an anisotropic conductive film formed on a substrate. Figure 4 (A) is a diagram schematically showing an example of a mask in which the opening window portion is a quadrilateral. Figure 4 (B) is a diagram schematically showing an example of irradiation of laser light passing through the opening of the mask. Figure 3 and Figure 4In the embodiment, the mask has one opening, but it is ideal to have a plurality of openings arranged at a predetermined pitch.
[0115] First, if Figure 3 As shown in (A), an anisotropic conductive film substrate 30 having an anisotropic conductive film 32 formed on a base material 31 is prepared. Figure 3 (B) and Figure 4 As shown in (B), the anisotropic conductive film substrate 30 is turned over, and laser light is irradiated from the substrate 31 side, and the quadrilateral removal portion 33 of the anisotropic conductive film 32 is peeled off by the laser light passing through the quadrilateral window portion of the mask opening. Then, as shown in FIG. Figure 4 As shown in (B), the range of the quadrilateral removal portion 33 is moved in the first direction D1 to form an anisotropic conductive film having the first direction D1 of the mask as the long dimension direction and the second direction D2 perpendicular to the first direction D1 as the short dimension direction.
[0116] Then, if Figure 3 (C) and Figure 4 As shown in (B), with respect to the anisotropic conductive film having the first direction D1 as the long dimension direction and the second direction D2 orthogonal to the first direction D1 as the short dimension direction, the range of the quadrilateral removal portion 33 is moved in the second direction D2. Figure 3 As shown in (D), a quadrilateral single piece 34 having a predetermined width in the first direction D1 and a predetermined width in the second direction D2 can be formed.
[0117] When the range of the quadrilateral removal portion 33 is moved in the first direction or the second direction, the range of the quadrilateral removal portion 33 is preferably overlapped. This can suppress the generation of burrs during single-piece processing and can suppress curling and chipping during single-piece transfer.
[0118] Figure 5 (A) is a microscope photograph showing an example of a wafer in which burrs are generated during wafer processing. Figure 5 (B) is a microscope photograph showing an example of a single sheet with curling and defect generated during single sheet transfer. When the range of the removal portion is moved, if the overlap of the range of the removal portion is insufficient, sometimes Figure 5 As shown in (A), a single piece 41 with burrs formed at the boundary of the range of the adjacent removal portion is formed. The single piece 41 with burrs is difficult to transfer to the accurate position, and becomes as shown in FIG. Figure 5 As shown in (B), curled single piece 42 and chipped single piece 43 are generated, resulting in a decrease in the transfer success rate.
[0119] [Specific example 2]
[0120] The manufacturing method of the single-piece film shown as specific example 2 is as follows: using a mask with a shading portion of a specified shape formed in an opening window portion, unnecessary portions of the anisotropic conductive film around the single piece are peeled off from the substrate, and a single piece of a specified shape is formed by the remaining portion of the anisotropic conductive film.
[0121] Figure 6 (A) is a diagram schematically showing an example of a mask having a light shielding portion in an opening window portion. Figure 6 (B) is a diagram schematically showing an example of irradiation of laser light passing through the opening of the mask. Figure 6 (A) and Figure 6 In (B), the mask has one opening, but it is ideal that a plurality of openings are arranged at a predetermined pitch.
[0122] First, similarly to Example 1, an anisotropic conductive film substrate having an anisotropic conductive film formed on a substrate is prepared, the anisotropic conductive film substrate is turned over, and laser light is irradiated from the substrate side, and the removed portion of the anisotropic conductive film is peeled off by the laser light that passes through the opening of the mask. Figure 6 As shown in (A), the opening of the mask has a quadrilateral light shielding portion 51 at the center of the quadrilateral window portion, so the removed portion becomes a ring with a quadrilateral hole at the center of the quadrilateral. Then, as Figure 6 As shown in (B), the range of the quadrilateral removal portion is moved in a first direction and a second direction perpendicular to the first direction, thereby forming a quadrilateral single piece 52 having a predetermined width in the first direction and a predetermined width in the second direction.
[0123] According to the method for manufacturing the single-piece film shown as Specific Example 2, the light shielding portion 51 for forming the single piece 52 in the window portion of the opening of the mask is provided, so that the anisotropic conductive film around the single piece 52 can be reliably removed. Therefore, the generation of burrs during single-piece processing can be prevented, and curling and defects during single-piece transfer can be suppressed.
[0124] Figure 7 FIG. 1 is a diagram schematically showing an example of a mask having a plurality of light shielding portions in an opening window portion. Figure 6 (A) and Figure 6 In (B), a light shielding portion is provided in the window of the opening of the mask, for example, Figure 7 As shown, in the window portion of the opening, a plurality of light shielding portions 53 are formed at a predetermined pitch in the X-axis direction and at a predetermined pitch in the Y-axis direction. The size of the window portion (W1×W2) can be determined based on the size of the mask and the maximum value of the effective range of laser irradiation. By using such a mask, a plurality of single pieces can be formed by a single laser irradiation.
[0125] [Example of opening shape]
[0126] Figure 8 is a diagram schematically showing an example of the shape of the opening of the mask, Figure 8 (A) represents a mask having a rectangular light shielding portion in the opening window portion, Figure 8 (B) represents a mask having a square light shielding portion in the opening window portion, Figure 8 (C) represents a mask having a rounded rectangular light shielding portion in the opening window portion, Figure 8 (D) shows a mask having a circular light shielding portion in the opening window portion.
[0127] As for the opening of the mask, it can be Figure 8 As shown in (A), a rectangular shading portion 54A is provided in the opening window portion, which can be Figure 8 As shown in (B), the light shielding portion 54B has a square shape, which can be Figure 8 The light shielding portion 54C having a rounded rectangular shape as shown in (C) can be as follows Figure 8 As shown in (D), there is a circular shading portion 54D. Thus, a rectangular single piece, a square single piece, a rounded rectangular single piece, and a circular single piece obtained by projecting the shape of the shading portion can be obtained. In addition, from the perspective of the processability of the single piece and the transfer using LLO, the shape of the shading portion is preferably a polygon formed by an obtuse angle (an angle greater than 90° and less than 180°), a rounded polygon, an ellipse, an oblong, a circle, or the like. When there is an acute angle in the shape of the shading portion, the processability of the single piece will deteriorate. In addition, when the single piece is transferred using LLO, the frequency of curling and defects in the single piece increases.
[0128] <2. Single film>
[0129] The monolithic film of this embodiment can be obtained by the above-mentioned method for manufacturing the monolithic film. That is, the monolithic film comprises a substrate and a monolithic film of a predetermined shape composed of an anisotropic conductive film. Here, the thickness of the anisotropic conductive film, the melt viscosity of the anisotropic conductive film at 30° C., and the ratio of the conductive particles to the reference value are within the above-mentioned ranges.
[0130] As for the shape of the single piece, as described above, in order to suppress curling and defects when transferring the single piece using LLO, it is preferably selected from at least one of a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle. In addition, as for the substrate, as described above, any substrate that is transmissive to laser light can be used, and quartz glass that has high transmittance over all wavelengths is preferred.
[0131] The size (length × width) of the single chip is appropriately set according to the size of the electronic component to be connected, and the ratio of the area of the single chip to the area of the electronic component is not particularly limited. If the area of the single chip is too large, the film that does not participate in the connection will become relatively wide, which may affect the optical properties of the structure. Therefore, the upper limit of the ratio of the area of the single chip to the area of the electronic component is 5.0 or less, preferably 4.0 or less, more preferably 3.2 or less, and further more preferably 2.4 or less. In addition, if the area of the single chip is too small, the allowable range of the landing accuracy of the micro-LED becomes narrower and the productivity may deteriorate. Therefore, the lower limit of the ratio of the area of the single chip to the area of the electronic component is 0.5 or more, preferably 0.8 or more, and further preferably 1.2 or more. These ratios can be appropriately designed according to the purpose of the structure. In addition, the thickness of the single chip is preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 6 μm or less, and further preferably 2 μm or more and 4 μm or less, like the thickness of the anisotropic conductive film. The thickness of the single piece can be measured using a known micrometer, digital thickness gauge, or laser displacement meter. For example, the thickness can be calculated by measuring 10 or more locations and averaging. The size of the single piece is preferably the same for all pieces, but there may be multiple pieces to increase the design freedom of the connection structure.
[0132] In addition, the distance between the monolithic sheets on the substrate is preferably more than 3 μm, more preferably more than 5 μm, and more preferably more than 10 μm. In addition, the upper limit of the distance between the monolithic sheets is preferably less than 3000 μm, more preferably less than 1000 μm, and more preferably less than 500 μm. When the distance between the monolithic sheets is too small, it is difficult to transfer the monolithic sheets. When the distance between the monolithic sheets is too large, it is preferred to paste the monolithic sheets. The distance between the monolithic sheets can be measured using a microscope (optical microscope, metal microscope, electron microscope, etc.).
[0133] <3. Method for manufacturing display device>
[0134] The manufacturing method of the display device of this embodiment comprises: a forming step of irradiating an anisotropic conductive film provided on a substrate with laser light from the substrate side, removing the anisotropic conductive film of the irradiated portion, and forming a single piece of a predetermined shape composed of the anisotropic conductive film on the substrate; a transfer step of transferring the single piece of the predetermined shape to a predetermined position of a wiring substrate or an electrode surface of a light-emitting element; and a mounting step of mounting the light-emitting element on the wiring substrate via the transferred single piece. Thus, excellent processability of the single piece can be obtained, and the takt time can be shortened.
[0135] The shape of the single piece is formed in a manner corresponding to the shape of the electrodes of the wiring substrate and the light-emitting element. As described above, in order to suppress the processability of the single piece and the curling and defects generated when the single piece is transferred by LLO, it is preferably selected from at least one of a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle.
[0136] A single chip can be arranged in a pixel unit (for example, a pixel unit of a group of RGB), that is, in a plurality of light-emitting element units, or in a sub-pixel unit (for example, an arbitrary RGB unit) constituting a pixel, that is, in a light-emitting element unit. Thus, it can correspond to a light-emitting element array ranging from a high PPI (Pixels Per Inch) to a low PPI light-emitting element array. In addition, for example, when RGB is set as one pixel, three sub-pixels are arranged as a group, or a total of six sub-pixels including three sub-pixels of a redundant circuit of RGB are arranged as a group, so a single chip can be arranged in a group of six sub-pixel units.
[0137] Alternatively, the individual chips may be arranged in units of electrodes corresponding to the first conductivity type electrode on the p side or the second conductivity type electrode on the n side of the light emitting element. Alternatively, to improve productivity, the individual chips may be arranged in units of, for example, 1 mm x 1 mm, within a range that does not impair transparency.
[0138] In addition, in the formation process, in order to efficiently remove unnecessary parts of the anisotropic conductive film, the anisotropic conductive film can be pre-treated. As pre-treatment, for example, there can be listed: a single-piece shaped incision of the light-emitting element unit and the electrode unit; a grid-shaped incision in which multiple longitudinal incisions and multiple transverse incisions intersect, etc. The incision can be set using a mechanical method, a chemical method, a laser, etc. It should be noted that the incision does not have to be deep enough to reach the substrate, and can be a half-cut. In this way, curling of the single piece can be suppressed.
[0139] In addition, the transfer method of the single chip in the transfer process is not particularly limited. For example, there can be listed a method of directly transferring the single chip from the substrate by the above-mentioned laser lift-off method (LLO method) and arranging it on a wiring substrate or a light-emitting element, and a method of transferring from a transfer material (mold material) to which the single chip is pre-attached and arranging it on a wiring substrate or a light-emitting element.
[0140] In addition, the method for configuring the light-emitting element in the installation process is not particularly limited. For example, there can be listed a method of configuring the light-emitting element on the wiring substrate by the above-mentioned laser lift-off method (LLO method), and a method of configuring the light-emitting element on the wiring substrate from a transfer material using a transfer material (mold material) to which the light-emitting element is pre-attached.
[0141] [First embodiment]
[0142] The manufacturing method of the display device of the first embodiment includes: a forming step (A1), using a laser lift-off device to remove the anisotropic conductive film of the laser irradiated portion, and forming a single piece of a specified shape composed of the anisotropic conductive film on a substrate; a transfer step (B1), using a laser lift-off device to transfer the single piece of a specified shape to a specified position of a wiring substrate; and a mounting step (C1), using a laser lift-off device to arrange the light-emitting element at a specified position of the wiring substrate, and mounting the light-emitting element on the wiring substrate.
[0143] Below, refer to Figures 9 to 12 , the following steps are described: a forming step (A1) of forming a single chip of a specified shape; a transfer step (B1) of transferring the single chip of a specified shape; and a mounting step (C1) of mounting the light-emitting element on a wiring substrate.
[0144] [Formation step (A1)]
[0145] In the forming step (A1), an anisotropic conductive film is prepared on a substrate, and the laser is irradiated from the substrate side using the laser lift-off device described above, and the removed portion of the anisotropic conductive film is lifted off by the laser that passes through the opening of the mask, thereby forming a single sheet. The method for forming a single sheet is the same as the method for manufacturing the single sheet film described above, so a detailed description is omitted here.
[0146] Fig. 9 2 is a cross-sectional view schematically showing an anisotropic conductive film provided on a substrate. Fig. 9 As shown, the anisotropic conductive film substrate includes a base material 61 and an anisotropic conductive film containing conductive particles 63, and an anisotropic conductive film 62 is provided on the base material 61. The base material 61 and the anisotropic conductive film 62 are the same as the base material 31 and the anisotropic conductive film 32 described above, and thus description thereof is omitted here.
[0147] In addition, from the viewpoint of improving ablation resistance, the conductive particles 63 preferably contain a metal having a melting point of 1400° C. or higher. From the viewpoint of easy availability, the upper limit of the melting point of the metal is preferably about 3500° C. In addition, from the viewpoint of easy availability, the metal constituting the conductive particles 63 preferably contains nickel, palladium, or ruthenium.
[0148] In addition, when the metal-coated resin particles formed by coating the surface of the resin particles with metal or the metal-coated inorganic particles formed by coating the surface of the inorganic particles with metal are used as the conductive particles 63, in order to minimize the influence of ablation on the resin particles and the inorganic particles, the metal coating thickness is preferably set to 0.08 μm or more, more preferably to 0.1 μm or more, particularly preferably to 0.15 μm or more, and most preferably to 0.2 μm or more. The upper limit of the metal coating thickness depends on the diameter of the conductive particles 63, and is preferably 20% of the diameter of the conductive particles 63 or about 0.5 μm.
[0149] [Transfer process (B)]
[0150] Fig.10 2 is a cross-sectional view schematically showing a state where a single film and a wiring substrate are placed opposite to each other. Fig.10 As shown, first, in the transfer step (A), the individual film 60 and the wiring substrate 70 are placed opposite to each other.
[0151] The monolithic film 60 includes a substrate 61 and monoliths 64 composed of an anisotropic conductive film containing conductive particles 63, and the monoliths 64 are arranged in light-emitting element units on the surface of the substrate 61. The substrate 61 can be any substrate that is transmissive to laser light, and preferably quartz glass having high light transmittance over all wavelengths.
[0152] The size (length × width) of the single chip 64 is appropriately set according to the size of the light-emitting element as a chip component, and the ratio of the area of the single chip 64 to the area of the light-emitting element is preferably 0.5 to 5.0, more preferably 0.5 to 4.0, and further preferably 0.5 to 2.0. In addition, the thickness of the single chip 64 is preferably 2 to 10 μm, more preferably 3 to 8 μm, and further preferably 4 to 6 μm or less. The size of the single chip is preferably the same for all, and there may be multiple types in order to increase the design freedom of the connection structure. Sometimes the single chip 64 is only provided on the electrode, in which case it can be interpreted as a conductive film. As a result, a connection structure with excellent light transmittance, conductivity and insulation that cannot be achieved by previous ACP (Anisotropic Conductive Paste), ACF (Anisotropic Conductive Film), NCF (Non Conductive Film), adhesives, etc. during connection can be obtained.
[0153] In addition, the distance between the monoliths arranged on the substrate 61 is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more. In addition, the upper limit of the distance between the monoliths is preferably 3000 μm or less, more preferably 1000 μm or less, and further preferably 500 μm or less. When the distance between the monoliths is too small, it is difficult to obtain excellent light transmittance and beauty. When the distance between the monoliths is too large, it is difficult to obtain a high PPI display device. The distance between the monoliths can be measured using a microscope (optical microscope, metal microscope, electron microscope, etc.).
[0154] The wiring substrate 70 has a circuit pattern for the first conductive type and a circuit pattern for the second conductive type on a substrate 71, and is configured in a manner that the light-emitting elements are arranged in units of sub-pixels (sub-pixels) constituting one pixel, for example, the first electrode 72 and the second electrode 73 are respectively provided at positions corresponding to the first conductive type electrode on the p side and the second conductive type electrode on the n side. In addition, the wiring substrate 70 forms a circuit pattern such as a data line and an address line of matrix wiring, and sets the light-emitting elements corresponding to each sub-pixel constituting one pixel to be able to be turned on and off. For example, one pixel can be composed of three sub-pixels of R (red), G (green), and B (blue), or it can be composed of four sub-pixels of RGBW (white) and RGBY (yellow), or it can be composed of two sub-pixels of RG and GB.
[0155] In addition, the wiring substrate 70 is preferably a light-transmitting substrate when used for transparent display, and the base material 71 is preferably glass, PET (Polyethylene Terephthalate), etc. The first electrode 72 and the second electrode 73 are preferably transparent conductive films such as ITO (Indium-Tin-Oxide), IZO (Indium-Zinc-Oxide), ZnO (Zinc-Oxide), and IGZO (Indium-Gallium-Zinc-Oxide).
[0156] Fig.11 2 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred to a predetermined position of a wiring substrate and arranged by irradiating a laser from the substrate side. Fig.11 As shown, in the transfer step (B), the laser lift-off device described above is used to irradiate the laser from the substrate 61 side, and the single piece 64 of the anisotropic conductive film is transferred to a predetermined position of the wiring substrate 70 for arrangement. By aligning the substrate 61 and the substrate 70 for transfer, the single piece 64 can be arranged on the substrate 70 in sub-pixel units.
[0157] Furthermore, when the size of the substrate 70 is larger than that of the base material 61 , the base material 61 is aligned multiple times to transfer the individual pieces 64 , so that the individual pieces 64 can be arranged in sub-pixel units in the screen area of the substrate 70 .
[0158] In the transfer of the single piece 64 of the anisotropic conductive film, the above-mentioned laser lift-off device can be used. Such a transfer method is called laser lift-off, for example, a method using ablation by laser. In the above-mentioned laser lift-off device, the single piece of film 60 as a donor substrate is maintained on a donor stage, and the wiring substrate 70 as an acceptor substrate is maintained on an acceptor stage. The distance between the single piece of film and the wiring substrate is preferably 10 to 20,000 μm, more preferably 50 to 1,500 μm, and further preferably 80 to 1,000 μm.
[0159] As the laser device, for example, an excimer laser oscillating a laser beam having a wavelength of 180 nm to 360 nm can be used. The oscillation wavelength of the excimer laser is, for example, 193 nm, 248 nm, 308 nm, or 351 nm, and can be appropriately selected from these oscillation wavelengths according to the light absorption of the material of the anisotropic conductive film.
[0160] The mask uses a pattern in which windows of a predetermined size are arranged at a predetermined pitch so that the projection on the boundary surface between the substrate 61 and the single piece 64 of the anisotropic conductive film is an arrangement of the desired laser light. In the mask, the pattern is applied to the substrate 61 by, for example, chrome plating, and the window portions where the chrome plating is not applied transmit the laser light, while the portions where the chrome plating is applied block the laser light.
[0161] The emitted light from the laser device is incident on the telescope optical system and transmitted to the laser scanner 11 in front of it. The laser light incident on the laser scanner 11 is adjusted by the telescope optical system to be substantially parallel light at any position within the moving range of the X-axis and Y-axis of the donor stage, so that it is incident on the laser scanner 11 with substantially the same size and the same angle (perpendicular).
[0162] The laser light that has passed through the laser scanner 11 is incident on the mask 12 via the field lens, and the laser light that has passed through the pattern of the mask 12 is incident on the projection lens 13. The laser light emitted from the projection lens 13 is incident on the substrate 61 side, and is accurately projected at the reduced size of the mask pattern to the position of the single piece 64 of the anisotropic conductive film formed on its surface (lower surface).
[0163] The pulse energy of the laser beam for imaging the interface between the single piece of anisotropic conductive film and the substrate is preferably 0.001 to 2 J, more preferably 0.01 to 1.5 J, and even more preferably 0.1 to 1 J. The fluence is preferably 0.001 to 2 J / cm 2 , more preferably 0.01 to 1 J / cm 2, more preferably 0.05 to 0.5 J / cm 2 The pulse width (irradiation time) is preferably 0.01 to 1×10 9 Picoseconds, more preferably 0.1 to 1×10 7 Picoseconds, more preferably 1 to 1×10 5 The pulse frequency is preferably 0.1 to 10,000 Hz, more preferably 1 to 1,000 Hz, and even more preferably 1 to 100 Hz. The number of irradiation pulses is preferably 1 to 30,000,000.
[0164] By using such a laser lift-off device, a shock wave is generated at the boundary between the substrate 61 and the single piece 64 of the anisotropic conductive film to which the laser is irradiated, and the single piece 64 is lifted off from the substrate 61 and transferred toward the wiring substrate 70, so that a plurality of single pieces 64 can be landed at predetermined positions on the wiring substrate 70. Thus, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the wiring substrate 70 with high precision and efficiency, and the cycle time can be shortened.
[0165] The reaction rate of the single piece 64 of the anisotropic conductive film after the transfer step (B1) is preferably 25% or less, more preferably 20% or less, and further preferably 15% or less. The reaction rate of the single piece 64 after the transfer step (B1) is 25% or less, so the light-emitting element can be thermally pressed in the mounting step (C1). As described above, the reaction rate can be determined by, for example, FT-IR.
[0166] In addition, the distance between the monolithic sheets arranged at the specified positions of the wiring substrate 70 is preferably 3 μm or more, more preferably 5 μm or more, and further preferably 10 μm or more, similarly to the distance between the monolithic sheets arranged on the substrate 61 of the monolithic film 60. In addition, the upper limit of the distance between the monolithic sheets is preferably 3000 μm or less, more preferably 1000 μm or less, and further preferably 500 μm or less. In the case where the distance between the monolithic sheets is too small, it is preferred to paste the anisotropic conductive film on the entire surface of the wiring substrate 70. In the case where the distance between the monolithic sheets is too large, it is preferred to paste the anisotropic conductive film on the specified positions of the wiring substrate 70. The distance between the monolithic sheets can be measured using a microscope (optical microscope, metal microscope, electron microscope, etc.).
[0167] [Installation process (C1)]
[0168] Fig.12 FIG. 1 is a cross-sectional view schematically showing a state where light emitting elements are mounted on a single chip arranged at a predetermined position on a wiring substrate. Fig.12 As shown, in the mounting step ( C1 ), the light emitting element 80 is mounted on the chip 64 arranged at a predetermined position on the wiring substrate 70 .
[0169] The light emitting element 80 includes a body 81, a first conductivity type electrode 82, and a second conductivity type electrode 83, and has a horizontal structure in which the first conductivity type electrode 82 and the second conductivity type electrode 83 are arranged on the same surface. The body 81 includes a first conductivity type cladding layer including, for example, n-GaN, a first conductivity type cladding layer including, for example, In x Al y Ga 1-x-y The active layer of the N layer, for example, the second conductive type cladding layer including p-GaN, has a so-called double heterostructure. The first conductive type electrode 82 is formed on a part of the first conductive type cladding layer through the passivation layer, and the second conductive type electrode 83 is formed on a part of the second conductive type cladding layer. When a voltage is applied between the first conductive type electrode 82 and the second conductive type electrode 83, carriers are concentrated in the active layer, and light emission occurs through recombination.
[0170] The light emitting elements 80 are arranged on the substrate 70 in a manner corresponding to the sub-pixels constituting one pixel, forming a light emitting element array. For example, one pixel can be composed of three sub-pixels of R (red), G (green), and B (blue), or four sub-pixels of RGBW (white) and RGBY (yellow), or two sub-pixels of RG and GB.
[0171] As a method of arranging sub-pixels, for example, in the case of RGB, stripe arrangement, mosaic arrangement, delta arrangement, etc. can be listed. Stripe arrangement arranges RGB in vertical stripes, which can achieve high precision. In addition, mosaic arrangement arranges the same colors of RGB diagonally, which can obtain a more natural image than stripe arrangement. In addition, delta arrangement arranges RGB in a triangle, and each point is offset by half a pitch for each field, which can obtain a natural image display.
[0172] In the mounting step (C1), the light emitting element 80 can be arranged at a predetermined position of the wiring substrate 70 using the above-mentioned laser lift-off device. In the above-mentioned laser lift-off device, the light emitting element as a donor substrate is held on a donor stage, and the wiring substrate 70 as an acceptor substrate is held on an acceptor stage. The distance between the light emitting element and the wiring substrate is preferably 10 to 1000 μm, more preferably 50 to 500 μm, and further preferably 80 to 200 μm.
[0173] As a method for connecting the light-emitting element 80 to the wiring substrate 70, a connection method known as thermocompression bonding, optical compression bonding, and thermo-optical compression bonding for anisotropic conductive films can be appropriately selected and used. In addition, when the conductive particles are solder particles, the connection can be made by reflow soldering. As conditions for thermocompression bonding, for example, a temperature of 150°C to 260°C, a pressure of 1MPa to 60MPa, and a time of 5 seconds to 300 seconds. By curing the anisotropic conductive film to form a cured film, the light-emitting element 80 can be anisotropically connected to the wiring substrate 70 in a state where there is no cured film between the light-emitting elements 80 and the wiring substrate 70 is exposed. In addition, by setting the wiring substrate 70 as a light-transmitting substrate, excellent light transmittance can be obtained compared to the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate 70.
[0174] [Modification of the first embodiment]
[0175] In the transfer step (B1) of the first embodiment described above, Fig.10 and Fig.11 As shown, the single piece 64 of the anisotropic conductive film is arranged on the wiring substrate 70 in sub-pixel units as light-emitting element units, but it is not limited to this. For example, it can be arranged in electrode units corresponding to the first conductive electrode on the p side or the second conductive electrode on the n side of the light-emitting element.
[0176] Fig.13 This is a cross-sectional view schematically showing a state in which a laser is irradiated from the substrate side, and a single piece of anisotropic conductive film is transferred to an electrode position on a wiring substrate and arranged. Fig.14 FIG. 1 is a cross-sectional view schematically showing a state where a light emitting element is mounted on a single chip arranged in electrode units on a wiring substrate. Fig.13 As shown, in the transfer process (B1), for example, the first single piece 64A is transferred to the first electrode 72 corresponding to the first conductive electrode 82 on the p side of the light-emitting element 80, and the second single piece 64B is transferred to the second electrode 73 corresponding to the second conductive electrode 83 on the n side of the light-emitting element 80.
[0177] The size (length × width) of the monolith 64A, 64B is appropriately set according to the size of the electrode of the light-emitting element, and there is no particular restriction on the ratio of the area of the monolith to the area of the electronic component. If it is too large, the film that does not participate in the connection will become relatively wide. The upper limit of the ratio of the area of the monolith to the area of the electrode is 5.0 or less, preferably 4.0 or less, more preferably 3.2 or less, and further preferably 2.4 or less. In addition, if it is too small, there is a concern that the connection will be unstable, so the lower limit of the ratio of the area of the monolith to the area of the electronic component is 0.5 or more, preferably 0.8 or more, and further preferably 1.2 or more. These ratios can be appropriately designed according to the purpose of the structure. In addition, the thickness of the monolith is preferably 2 to 10 μm, more preferably 3 to 8 μm, and further preferably 4 to 6 μm or less.
[0178] like Fig.14 As shown, in the mounting step (C1), the light emitting element 80 is mounted on the chips 64A and 64B arranged in electrode units on the wiring substrate 70. This can further improve the transparency of the display device.
[0179] As described above, according to the manufacturing method of the display device of the first embodiment, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the wiring substrate 70 with high precision and efficiency by irradiation of laser, so that the takt time can be shortened. In addition, excellent light transmittance, conductivity and insulation properties that cannot be achieved by conventional ACP, ACF, NCF, adhesives, etc. can be obtained during connection, and a high-brightness / high-definition transparent display can be obtained.
[0180] [Second embodiment]
[0181] The manufacturing method of the display device of the second embodiment comprises: a forming step (A2), using a laser lift-off device to remove the anisotropic conductive film of the laser irradiated portion, and forming a single piece of a predetermined shape composed of the anisotropic conductive film on a substrate; a transfer step (B2-1), using a laser lift-off device to transfer the single piece of a predetermined shape to the electrode surface of the light-emitting element; a re-transfer step (B2-2), using a laser lift-off device to re-transfer the light-emitting element to which the single piece has been transferred to a predetermined position of a wiring substrate; and a mounting step (C2), mounting the light-emitting element on the wiring substrate. Thus, the excellent processability and transferability of the single piece can be obtained, and the takt time can be shortened.
[0182] Below, refer to Figure 15 to Figure 17, the following steps are described: a forming step (A2) of forming a single chip of a specified shape; a transfer step (B2-1) of transferring the single chip of a specified shape to the electrode surface of the light-emitting element; a re-transfer step (B2-2) of re-transferring the light-emitting element to which the single chip has been transferred to a specified position of the wiring substrate; and a mounting step (C2) of mounting the light-emitting element on the wiring substrate. It should be noted that in the same configuration as the first embodiment, the same symbols are marked and the description is omitted.
[0183] [Formation step (A2)]
[0184] The forming step (A2) is the same as the forming step (A1) of the first embodiment, and therefore a detailed description thereof will be omitted here.
[0185] [Transfer process (B2-1)]
[0186] Fig.15 FIG. 1 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film provided on a substrate and light-emitting elements arranged on a transfer substrate are placed opposite to each other. Fig.15 As shown, in the transfer step (B2), the single piece 64 of the anisotropic conductive film provided on the base material 61 is placed opposite to the transfer substrate 90. The single piece 64 is formed on the base material 61 in a shape corresponding to the electrode of the light emitting element 50.
[0187] The transfer substrate 90 includes a base material 91 and light emitting elements 80 arranged on the base material 91. The base material 91 is appropriately selected according to the transfer method of the re-transfer step (B2-2) described later. For example, in the re-transfer step (B2-2) described later, when a transfer method using ablation by laser is used, the base material 91 can be any base material that is transmissive to the laser, and preferably quartz glass having high light transmittance at all wavelengths. In addition, for example, in the re-transfer step (B2-2) described later, when the transfer substrate 90 is attached to the wiring substrate 20 and the light emitting element 80 is transferred, the base material 91 can have, for example, a silicone rubber layer.
[0188] In the transfer step (B2-1), similarly to the above-described first embodiment, for example, a transfer method using ablation with laser light, called laser lift-off, can be used.
[0189] Fig.16 2 is a cross-sectional view schematically showing a state in which a single piece of anisotropic conductive film is transferred onto a light-emitting element arranged on a transfer substrate by irradiating a laser from the substrate side. Fig.16 As shown, in the transfer step ( B2 - 1 ), laser light is irradiated from the base material 61 side to transfer the single piece 64 of the anisotropic conductive film onto the light emitting element 80 arranged on the transfer substrate 90 .
[0190] As in the first embodiment described above, the laser lift-off device described above can be used in the transfer of the anisotropic conductive film single piece 64. By using the laser lift-off device, a shock wave is generated at the boundary surface between the substrate 61 and the single piece 64 of the anisotropic conductive film to the single piece 64 irradiated with laser, and a plurality of single pieces 64 are peeled off from the substrate 61 and transferred toward the light emitting element 80 arranged on the transfer substrate, so that the single piece 64 can be landed on the light emitting element 80 with high precision.
[0191] [Re-transfer process (B2-2)]
[0192] Fig.17 FIG. 2 is a cross-sectional view schematically showing a state where the light-emitting element having been transferred to a single chip is transferred to a wiring substrate. Fig.17 As shown, in the re-transfer process (B2-2), the light emitting element 80 to which the single chip 64 is transferred is re-transferred onto the wiring substrate 70. The re-transfer method is not particularly limited, and examples thereof include a method in which the light emitting element 80 to which the single chip 64 is transferred is directly transferred from a transfer substrate 90 by a laser lift-off method (LLO method) and arranged on the wiring substrate 70, a method in which the light emitting element 80 is transferred from a transfer substrate 90 to which the light emitting element 80 to which the single chip 64 is transferred is previously closely attached and arranged on the wiring substrate 70, and the like.
[0193] In the re-transfer process (B2-2), the light emitting element 80 is preferably transferred in units of sub-pixels constituting one pixel. This allows the light emitting element array to be adapted from a high PPI (Pixels Per Inch) light emitting element array to a low PPI light emitting element array.
[0194] [Installation process (C2)]
[0195] In the mounting step (C2), the arranged light emitting elements 80 are mounted on a predetermined position of the wiring substrate 70 via the wafer 64. The state in which the light emitting elements 80 are mounted is similar to that in the embodiment of FIG. Fig.12 The method of connecting the light emitting element 80 to the wiring substrate 70 is the same as that of the first embodiment. Thus, the light emitting element 80 can be anisotropically connected to the wiring substrate 70 in a state where there is no anisotropic conductive film between the light emitting elements 80 and the wiring substrate 70 is exposed. In addition, by setting the wiring substrate 70 as a light-transmitting substrate, compared with the case where the anisotropic conductive film is attached to the entire surface of the wiring substrate 70, excellent light transmittance can be obtained.
[0196] [Modification of the Second Embodiment]
[0197] In the transfer step (B2-1) of the second embodiment described above, Fig.15 and Fig.16As shown, the single piece 64 of the anisotropic conductive film is transferred to the light emitting element 80, but it is not limited to this. For example, the single piece of the anisotropic conductive film can be transferred to the light emitting element in electrode units. Fig.14 As in the modified example of the first embodiment shown in the figure, for example, the first single piece is transferred to the first conductive electrode 82 on the p-side of the light emitting element 80 and mounted, and the second single piece is transferred to the second conductive electrode 83 on the n-side of the light emitting element 80 and mounted. This can further improve the transparency of the display device.
[0198] As described above, according to the manufacturing method of the display device of the second embodiment, the single piece 64 of the anisotropic conductive film can be transferred and arranged on the light emitting element 80 with high precision and efficiency by irradiation with laser, so that the takt time can be shortened. In addition, excellent light transmittance, conductivity and insulation properties that cannot be achieved by conventional ACP, ACF, NCF, adhesives, etc. during connection can be obtained, and a high-brightness / high-definition transparent display can be obtained.
[0199] [Repair process]
[0200] In the display device of the above-mentioned embodiment, for example, when there is a light-emitting element that does not light up, the following repair can be performed: after removing the light-emitting element that does not light up using the above-mentioned laser lift-off device, the single piece of the anisotropic conductive film is transferred to the portion again to install the light-emitting element. In the laser lift-off device, the display device having a wiring substrate on which light-emitting elements are arranged is held on a donor stage, and laser light is irradiated from the wiring substrate side to lift off the desired light-emitting element and single piece, and the light-emitting element and single piece lifted off from the wiring substrate are received by the acceptor substrate. In this embodiment, the wiring substrate is exposed between the single pieces, so the repair is preferably performed in single piece units.
[0201] In addition, in the above-mentioned embodiment, a method for manufacturing a display device as a display is cited as an example, but the present technology is not limited to this, and can also be applied to a method for manufacturing a light-emitting device as a light source. In addition, it can also be applied to a method for manufacturing a connection structure that connects a first electronic component and a second electronic component. That is, the method for manufacturing a connection structure has: a forming step, irradiating an anisotropic conductive film provided on a substrate with a laser from the substrate side, removing the anisotropic conductive film of the irradiated portion, and forming a single piece of a prescribed shape composed of the anisotropic conductive film on the substrate; a transfer step, transferring the single piece of a prescribed shape to a prescribed position of the first electronic component; and a mounting step, mounting the second electronic component on a wiring substrate via the transferred single piece, the thickness of the anisotropic conductive film being greater than 0.9 times and less than 8 times the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C being greater than 2000 Pa·s and less than 800000 Pa·s. As the first electronic component and the second electronic component, for example, light-emitting elements, IC (Integrated Circuit), flexible substrate (FPC: Flexible Printed Circuits), LCD (Liquid Crystal Display) panels, organic EL (OLED) and other flat panel display (FPD) applications, touch panel applications, transparent substrates, printed circuit boards (PWB), etc. are listed. The material of the printed circuit board is not particularly limited, for example, it can be glass epoxy resin such as FR-4 substrate, plastics such as thermoplastic resin, ceramics, etc. can also be used. In addition, the transparent substrate is not particularly limited as long as it has high transparency, and glass substrates, plastic substrates, etc. can be listed.
[0202] <4. Display device>
[0203] The display device of this embodiment can be obtained by the manufacturing method of the display device described above. That is, the display device includes: a plurality of light-emitting elements; a wiring substrate for arranging the light-emitting elements; and a cured film for connecting the plurality of light-emitting elements and the wiring substrate, the cured film being a single piece of a predetermined shape composed of the anisotropic conductive film described above cured.
[0204] The shape of the single piece is preferably at least one selected from a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle. Thus, the substrate can be exposed between the single pieces, and excellent light transmittance and beauty can be obtained.
[0205] As mentioned above Fig.12 and Fig.14 As shown, the display device includes: a plurality of light emitting elements 80 ; a substrate 70 on which the light emitting elements 80 are arranged; and a cured film connecting the plurality of light emitting elements 80 and the substrate 70 .
[0206] The cured film is formed by curing a single piece of anisotropic conductive film of a prescribed shape. The arrangement of the single pieces on the substrate 70 is not particularly limited as long as the light transmittance effect can be obtained, and preferably the sub-pixel units corresponding to the light-emitting elements 80. By arranging the single pieces in sub-pixel units, the exposed portion of the substrate between the single pieces can be increased, and very excellent light transmittance can be obtained. Preferably, when the single pieces are arranged in sub-pixel units, the area of the single piece of the exposed portion between each micro-LED is less than 3.2 times the area of the micro-LED, preferably less than 2.4 times, and more preferably less than 1.2 times. In addition, a plurality of light-emitting elements 80 near the sub-pixel unit can also be connected with one single piece. Thereby, the installation speed can be shortened (installation efficiency can be improved), and the range of allowable specifications can be expanded according to the transparency and color conditions of the substrate side.
[0207] The cured film of anisotropic conductive film is the same as anisotropic conductive film, and preferably conductive particles are arranged in order in the face direction. By making the conductive particles arranged in order in the face direction, the particle surface density becomes uniform, and the conductivity and insulation can be improved. As the state of conductive particles arranged in order in the face, for example, a plane lattice pattern having one or more arrangement axes of conductive particles arranged in a prescribed direction at a prescribed interval can be listed, and the plane lattice pattern can be listed as: rhombic lattice, hexagonal lattice, square lattice, rectangular lattice, parallel body lattice, etc. The conductive particles are arranged in order in the face direction, and it can also be said that the conductive particles are arranged in the top view of the film. In addition, the arrangement of the face direction of the conductive particles can be random, or there can be a plurality of regions with different plane lattice patterns.
[0208] The particle surface density of the cured film of the anisotropic conductive film can be appropriately designed according to the electrode size of the light-emitting element 80, and the lower limit of the particle surface density can be set to 500 particles / mm. 2 Above, 20000 pieces / mm 2 Above, 40000 pieces / mm 2 Above, 50000 pieces / mm 2 The upper limit of the particle surface density can be set to 1500000 particles / mm 2 Below, 1,000,000 pieces / mm 2 Below, 500,000 pieces / mm 2 Below, 100,000 pieces / mm 2 As a result, even when the size of the electrodes of the light emitting element 80 is small, excellent conductivity and insulation properties can be obtained.
[0209] The particle surface density of the cured film of anisotropic conductive film is the surface density of conductive particles when filming is performed during manufacture. The particle surface density is the same whether the randomly configured part is measured or the arranged part is measured. In the case of obtaining the particle number density from a plurality of monoliths, the particle surface density can be obtained based on the area and the number of particles obtained by removing the space between the monoliths from the area of the space including the monoliths. Monoliths are sometimes not suitable for being represented by number density, and sometimes are suitable for being represented by the occupied area ratio, particle diameter, center distance between particles, and number of particles in a monolith.
[0210] It should be noted that the particle surface density of the cured film of the anisotropic conductive film is the surface density of the conductive particles when the film is formed during manufacture. The particle surface density is the same whether the randomly configured part is measured or the arranged part is measured. In the case where the particle number density is obtained by multiple monoliths, the particle surface density can be obtained based on the area and particle number obtained by removing the space between the monoliths from the area of the space including the monolith. Monoliths are sometimes not suitable for being represented by number density, and are sometimes suitable for being represented by the occupied area ratio, particle diameter, center distance between particles, and number of particles in a monolith.
[0211] The number of conductive particles in each single piece can be appropriately designed according to the electrode size of the light-emitting element 80. The lower limit is, for example, more than 2, preferably more than 4, and more preferably more than 10, and the upper limit is less than 6000, preferably less than 500, and more preferably less than 100.
[0212] The average transmittance of visible light after the monolithic sheet is placed (set) on the substrate is preferably 20% or more, more preferably 35% or more, and further preferably 50% or more. Thus, a display device with excellent light transmittance and good appearance can be obtained. Even in the case of a non-transparent substrate, the monolithic sheet can be pasted on plain glass or a transparent substrate for evaluation, and the average transmittance can be calculated using it as a reference (Ref). The average transmittance of visible light with a light-emitting element becomes even lower. When a light-emitting element is installed, the average transmittance measured in an unlit state is used. The average transmittance of visible light can be measured, for example, using an ultraviolet-visible spectrophotometer.
[0213] As far as the size of the single chip relative to the size of the light emitting element is concerned, the size of the single chip can be smaller than the size of the light emitting element 80 as long as conductivity is achieved. In addition, as long as the light transmittance effect of the display device is achieved, the single chip can be configured to exist not directly under the light emitting element but at the peripheral portion.
[0214] The amount of a single chip protruding from the light emitting element 80 is preferably less than 30 μm, more preferably less than 10 μm, and further preferably less than 5 μm. In addition, when the single chip does not protrude, the protruding amount may be zero or a negative number. Thus, compared with the configuration example of a display device in which a cured film is provided on the entire surface of the substrate, an excellent light transmittance can be obtained. It should be noted that the amount of a single chip protruding from the light emitting element 80 is the maximum value of the distance from the periphery of the light emitting element 80 to the periphery of the single chip.
[0215] According to the display device of this embodiment, by having an exposed portion of the substrate 70 between the single pieces of the cured film, excellent light transmittance, conductivity and insulation can be obtained, which cannot be achieved when the previous ACP, ACF, NCF, adhesive, etc. are provided on the entire surface, and a high-brightness / high-definition transparent display can be obtained.
[0216] It should be noted that, in the above-mentioned embodiment, a display device as a display obtained by arranging the light-emitting elements 80 in sub-pixel units is cited as an example, but the present technology is not limited to this, and can also be applied to a light-emitting device as a light source. The light-emitting device includes: a plurality of light-emitting elements; a substrate on which the light-emitting elements are arranged; and a cured film connecting the plurality of light-emitting elements and the substrate, the cured film being composed of a plurality of single pieces and having an exposed portion where the substrate is exposed between the single pieces. According to such a light-emitting device, the light-emitting element 80 is of a micro size, and the number of chips obtained per wafer increases, so that the price can be reduced, and in addition, industrial advantages such as thinning and energy saving of the light-emitting device can be obtained.
[0217] In addition, the present technology can also be applied to a connection structure connecting a first electronic component and a second electronic component. That is, the connection structure comprises: a first electronic component; a second electronic component; and a cured film, the first electronic component and the second electronic component are connected, the cured film is formed by curing a single piece of a predetermined shape composed of an anisotropic conductive film, the thickness of the anisotropic conductive film is 0.9 times or more and 8 times or less of the particle size of the conductive particles in the anisotropic conductive film, and the melt viscosity of the anisotropic conductive film at 30°C is 2000 Pa·s or more and 800000 Pa·s or less.
[0218] Example
[0219] <3. Example>
[0220] In this embodiment, an anisotropic conductive film having a specified thickness, a specified particle configuration, a specified orderly arrangement of particles, and a specified melt viscosity is processed into a single piece, and the shape state of the single piece is evaluated. In addition, the lighting evaluation is performed on the mounted body obtained by mounting a μLED element using the processed single piece. It should be noted that the present technology is not limited to these embodiments.
[0221] [Measurement of Melt Viscosity of Anisotropic Conductive Film]
[0222] The melt viscosity of the anisotropic conductive film at 30° C. was measured under the following measurement conditions using a rheometer (HAAKE MARS, manufactured by Thermo Fisher Scientific). The anisotropic conductive films were stacked to form a sample having a thickness of 300 μm, and the measurement was performed.
[0223] Measurement conditions: glass-coated polypropylene container (PP08, Φ8 mm), frequency 10 Hz.
[0224] [Calculation of the Existence Ratio of Conductive Particles Relative to the Baseline]
[0225] The cross section of the anisotropic conductive film is observed under a microscope, and the center positions of the conductive particles in the thickness direction within a specified range of more than 200 conductive particles are measured. The average value is set as a baseline, and the proportion of conductive particles whose outer diameter partly touches the baseline within the specified range is calculated.
[0226] [Single-sheet processing of anisotropic conductive films]
[0227] Using a laser lift-off device (LUM-XTR manufactured by Shin-Etsu Engineering), laser was irradiated from the quartz glass side of the anisotropic conductive film bonded to a 4-inch quartz glass, and the unnecessary portion was transferred to the plain glass, thereby forming a single piece of anisotropic conductive film on the quartz glass. Figure 2 As shown, the laser stripping device, for example, includes: a laser scanner for scanning the optical axis of the laser; a mask having a plurality of openings of a specified shape arranged at a specified interval; a projection lens for reducing and projecting the laser onto a donor substrate; a donor stage for holding the donor substrate; and an acceptor stage for holding the acceptor substrate, wherein an anisotropic conductive film substrate serving as the donor substrate is held on the donor stage, and plain glass serving as the acceptor substrate is held on the acceptor stage, and the distance between the anisotropic conductive film and the plain glass is set to 100 μm.
[0228] The laser device used an excimer laser with an oscillation wavelength of 248 nm. The laser pulse energy was 600 mJ and the fluence was 250 mJ / cm 2 , the pulse width (irradiation time) is 30000 picoseconds, the pulse frequency is 0.01kHz, and the number of irradiation pulses is set to one pulse per single chip.
[0229] The pulse energy of the laser beam used to irradiate the interface between the anisotropic conductive film and the quartz glass for imaging is 0.001 to 2 J, and the fluence is 0.001 to 2 J / cm 2 , pulse width (irradiation time) is 0.01~1×10 9Picoseconds, the pulse frequency is 0.1 to 10,000 Hz, and the number of irradiation pulses is preferably 1 to 30,000,000.
[0230] The mask uses a pattern of circular light shielding portions in the shape of a single piece, so that the projection of the anisotropic conductive film substrate as the donor substrate on the interface with the quartz glass becomes an arrangement of the size of a single piece (circle with a diameter of 80 μm) with a width of 158 μm and a length of 158 μm. The anisotropic conductive film is punched through the mask to form a plurality of circular single pieces with a diameter of 80 μm on the quartz glass.
[0231] [Evaluation of the shape of a single piece]
[0232] After the anisotropic conductive film was processed into single sheets, 1000 pieces were randomly selected from the single sheets (a total of 10000 pieces), and the single sheets with normal shape (no curling or defect) were visually inspected under a microscope (for curling or defect, refer to the above-mentioned Figure 5 The curled single pieces 42 and the defective single pieces 43 shown in (B) are counted. Then, the shape normality rate is calculated by the following formula. The shape normality rate is preferably 85% or more, more preferably 95% or more, and more preferably 99% or more.
[0233] Normal shape rate = number of normal shape single pieces / number of mother pieces × 100
[0234] [Evaluation of lighting test]
[0235] Furthermore, a lighting evaluation was performed on a mounted body obtained by using the processed monolithic mounted μLED element. The mounted body was prepared and the lighting evaluation was performed as follows.
[0236] (Manufacturing of mounting body)
[0237] Fig.18 is a diagram schematically showing a method for manufacturing a mounting body, Fig.18 (A) indicates the process of preparing a single piece. Fig.18 (B) represents the process of transferring the single piece to the substrate, Fig.18 (C) represents the process of temporarily fixing the μLED element. Fig.18 (D) shows the process of crimping the μLED element. Fig.19 is a top view schematically showing an evaluation substrate used for a lighting test, Fig. 20 (A) is a top view schematically showing an electrode surface of a μLED element. Fig. 20 (B) is a diagram schematically showing a state where a μLED element is mounted on an evaluation substrate.
[0238] like Fig.18As shown in (A), first, prepare the single piece 104 of a predetermined shape processed on the quartz glass 101 as described above, as shown in FIG. Fig.18 As shown in (B), laser light is irradiated from the back side (quartz glass 101 side) of the single piece 104 to transfer the single piece 104 to a predetermined position of the evaluation substrate 107. The transfer of the single piece 104 is performed in the same manner as LLO in the evaluation of the single piece transfer described above.
[0239] The evaluation substrate 107 has a wiring pattern formed on a glass substrate with a thickness of 0.5 mm, with a base of Cr having a thickness of 20 nm and a surface of Au having a thickness of 80 nm. As shown in FIG. 27 , an electrode group including 15 groups of first comb-shaped electrodes 107A with 6 comb teeth and a second comb-shaped electrode 107B with 6 comb teeth is used. The wiring pattern is as shown in FIG. Fig.19 and Fig. 20 As shown in (B), a wiring pattern with a comb line width of 90 μm, a spacing width of 12 μm or 24 μm, and each channel of approximately 1300 μm×15ch≈19.3 mm is used to transfer a single piece of a specified shape between wirings with a spacing width of 12 μm.
[0240] Then, if Fig.18 As shown in (C), a polydimethylsiloxane (PDMS) sheet 109 having μLED elements 108 arranged on the convex portion by LLO is pre-aligned and bonded under the conditions of 30°C-30MPa-10se, as shown in FIG. Fig. 20 As shown in (B), the μLED element 108 is temporarily fixed between wirings with a spacing width of 12 μm on the evaluation substrate 107 via the single chip 104 .
[0241] like Fig. 20 As shown in (A), the μLED element 108 used is an element having an outer diameter of 34 μm×58 μm, a first electrode 108A and a second electrode 108B of 27 μm×18 μm, and a distance between the first electrode 108A and the second electrode 108B of 16 μm.
[0242] Then, if Fig.18 As shown in (D), the μLED elements 108 were pressed together by applying pressure under the pressing conditions of 150° C.-150 N-30 sec, thereby producing a mounted body having μLED elements (3600 pieces in total).
[0243] (Light up the review)
[0244] A voltage of 3.0 V was applied to the first and second comb-shaped electrodes of the mounting body, the number of lit μLED elements (3600 pcs in total) was counted, and the lighting rate was calculated by the following formula: The lighting rate was preferably 95% or more.
[0245] Lighting rate = number of lights / number of cells × 100
[0246] [Example 1]
[0247] (Fabrication of anisotropic conductive film)
[0248] An adhesive is prepared by mixing 35 parts by mass of a phenoxy resin (trade name: PKHH, manufactured by Basho Chemical Industry Co., Ltd.), 50 parts by mass of a high-purity bisphenol A epoxy resin (trade name: YL-980, manufactured by Mitsubishi Chemical Co., Ltd.), 5 parts by mass of a hydrophobic silica (trade name: R202, manufactured by Nippon AEROSIL Co., Ltd.), 7 parts by mass of a cationic polymerization initiator (trade name: SI-60L, manufactured by Sanshin Chemical Industry Co., Ltd.) and 3 parts by mass of a silane coupling agent (trade name: KBM-503, manufactured by Shin-Etsu Silicone Co., Ltd.).
[0249] The adhesive was applied on a 50 μm thick PET film and dried to form a 4 μm thick resin film. 2 The conductive particles (average particle size 2.2 μm, resin core metal coated particles, Ni plating thickness 0.1 μm, manufactured by Sekisui Chemical Co., Ltd.) are arranged in a hexagonal lattice and bonded to a resin film, and the conductive particles are pressed into the resin film for transfer, thereby producing an anisotropic conductive film in which the conductive particles are orderly arranged. Then, the conductive particle transfer surface of the anisotropic conductive film is bonded to quartz glass, such as Figure 1 As shown in (A), an anisotropic conductive film substrate is produced in a state where the reference value is close to the base material side.
[0250] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 1 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 1 was 99% or more, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 99% or more.
[0251] [Example 2]
[0252] An anisotropic conductive film substrate was produced in the same manner as in Example 1 except that a resin film having a thickness of 2 μm was formed to produce an anisotropic conductive film in which conductive particles were orderly arranged.
[0253] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 2 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 99%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 2 was 99% or more, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 99% or more.
[0254] [Example 3]
[0255] An anisotropic conductive film substrate was produced in the same manner as in Example 1 except that a resin film having a thickness of 10 μm was formed to produce an anisotropic conductive film in which conductive particles were orderly arranged.
[0256] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 3 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 90%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 3 was 95%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 95%.
[0257] [Example 4]
[0258] The side of the anisotropic conductive film opposite to the conductive particle transfer surface is attached to a quartz glass. Figure 1 An anisotropic conductive film substrate was produced in the same manner as in Example 1 except that the reference value was closer to the opposite surface side of the substrate as shown in (B).
[0259] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 4 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 4 was 99% or more, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 99% or more.
[0260] [Example 5]
[0261] An anisotropic conductive film substrate was prepared in the same manner as in Example 1 except that the amount of phenoxy resin was reduced and the amount of high-purity bisphenol A epoxy resin was increased to produce an anisotropic conductive film having a melt viscosity of 2000 Pa·s at 30°C.
[0262] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 5 at 30°C was 2000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 5 was 98%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 98%.
[0263] [Example 6]
[0264] An anisotropic conductive film substrate was prepared in the same manner as in Example 1 except that the amount of phenoxy resin was increased and the amount of high-purity bisphenol A epoxy resin was reduced to produce an anisotropic conductive film having a melt viscosity of 800,000 Pa·s at 30°C.
[0265] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Example 6 at 30°C was 800,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 6 was 97%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 97%.
[0266] [Example 7]
[0267] The particle density is 58000pcs / mm 2 An anisotropic conductive film in which the conductive particles are randomly arranged is produced by adhering a sheet of randomly arranged conductive particles (average particle size 2.2 μm, resin core metal-coated particles, Ni plating thickness 0.1 μm, manufactured by Sekisui Chemical Co., Ltd.) to a resin film, and the conductive particles are pressed into the resin film for transfer, thereby producing an anisotropic conductive film in which the conductive particles are randomly arranged. Otherwise, an anisotropic conductive film substrate is produced in the same manner as in Example 1.
[0268] As shown in Table 2, the melt viscosity of the anisotropic conductive film of Example 7 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 7 was 88%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 86%.
[0269] [Example 8]
[0270] The side of the anisotropic conductive film opposite to the conductive particle transfer surface is attached to a quartz glass. Figure 1 An anisotropic conductive film substrate was produced in the same manner as in Example 7 except that the reference value was closer to the opposite surface side of the substrate as shown in (B).
[0271] As shown in Table 2, the melt viscosity of the anisotropic conductive film of Example 8 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Example 8 was 86%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 85%.
[0272] [Comparative Example 1]
[0273] An anisotropic conductive film substrate was produced in the same manner as in Example 1 except that a resin film having a thickness of 20 μm was formed to produce an anisotropic conductive film in which conductive particles were orderly arranged.
[0274] As shown in Table 2, the melt viscosity of the anisotropic conductive film of Comparative Example 1 at 30°C was 20,000 Pa·s. The abundance of conductive particles relative to the reference value was 95%. The shape regularity of the anisotropic conductive film substrate of Comparative Example 1 after the individual processing was 0%.
[0275] [Comparative Example 2]
[0276] In the adhesive, the particle density is 58000pcs / mm 2 Conductive particles (average particle size 2.2 μm, resin core metal coated particles, Ni plating thickness 0.1 μm, manufactured by Sekisui Chemical Co., Ltd.) were mixed in a manner to prepare an anisotropic conductive adhesive composition. Then, the anisotropic conductive adhesive composition was applied on a PET film having a thickness of 50 μm and dried. Figure 1 An anisotropic conductive film substrate was produced in the same manner as in Example 1 except that an anisotropic conductive film having a thickness of 4 μm in which the conductive particles in the anisotropic conductive film were dispersed in the thickness direction was formed as shown in (C).
[0277] As shown in Table 2, the melt viscosity of the anisotropic conductive film of Example 7 at 30°C was 20,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 70%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Comparative Example 2 was 73%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 70%.
[0278] [Comparative Example 3]
[0279] An anisotropic conductive film substrate was prepared in the same manner as in Example 1 except that the amount of phenoxy resin was reduced and the amount of high-purity bisphenol A epoxy resin was increased to produce an anisotropic conductive film having a melt viscosity of 1000 Pa·s at 30°C.
[0280] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Comparative Example 3 at 30°C was 1000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Comparative Example 3 was 80%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 80%.
[0281] [Comparative Example 4]
[0282] An anisotropic conductive film substrate was prepared in the same manner as in Example 1 except that the amount of phenoxy resin was increased and the amount of high-purity bisphenol A epoxy resin was reduced to produce an anisotropic conductive film having a melt viscosity of 1,000,000 Pa·s at 30°C.
[0283] As shown in Table 1, the melt viscosity of the anisotropic conductive film of Comparative Example 4 at 30°C was 1,000,000 Pa·s. In addition, the presence rate of the conductive particles relative to the reference value was 95%. The shape normality rate of the single piece after the single piece processing of the anisotropic conductive film substrate of Comparative Example 4 was 76%, and the lighting rate of the mounted body obtained by mounting the μLED element using the single piece was 76%.
[0284] Table 1 shows the evaluation results of the shape normality of Examples 1 to 6, and Table 2 shows the evaluation results of the shape normality of Examples 7 and 8 and Comparative Examples 1 to 4.
[0285] [Table 1]
[0286]
[0287] [Table 2]
[0288]
[0289] In Comparative Example 1, the thickness of the anisotropic conductive film is 20 μm, so the shape normality is 0%. It can be considered that this is because the thickness of the anisotropic conductive film is large, so the anisotropic conductive film is not torn. In Comparative Example 2, the conductive particles in the anisotropic conductive film are dispersed in the thickness direction, so the shape normality is not good. It can be considered that this is because there is unevenness in the degree of ablation. In Comparative Example 3, the melt viscosity of the anisotropic conductive film at 30°C is 1000 Pa·s, so a good shape normality cannot be obtained. It can be considered that this is because the melt viscosity of the anisotropic conductive film at 30°C is low, so the single piece will shrink after laser irradiation, and the single piece is difficult to maintain as a film. In Comparative Example 4, the melt viscosity of the anisotropic conductive film at 30°C is 1000000 Pa·s, so it can be considered that the film properties of the anisotropic conductive film are strong and difficult to remove by laser irradiation.
[0290] In Examples 1 to 8, the thickness of the anisotropic conductive film is 1 μm or more and 10 μm or less, the melt viscosity of the anisotropic conductive film at 30°C is 2000 Pa·s or more and 800000 Pa·s or less, and more than 90% of the conductive particles in the anisotropic conductive film are present in the average value of the center position of the conductive particles in the thickness direction, so a good shape normality is obtained. In addition, in Examples 1 to 6, the conductive particles in the anisotropic conductive film are arranged in an orderly manner in the surface direction, so a shape normality of more than 90% can be obtained. This is considered to be because the degree of ablation in the surface direction is uniform.
[0291] In addition, the outer shape of the single piece of Examples 1 to 8 in normal shape was observed by a metal microscope, and it was confirmed that the outer shape of the single piece was processed along the arrangement of the conductive particles. In other words, it was confirmed that the single piece was torn along the arrangement of the conductive particles. In addition, the lighting rate of the lighting test in Examples 1 to 8 was the same as the normal shape rate of the single piece.
[0292] Description of Reference Numerals
[0293] 1: substrate; 2A to 2C: anisotropic conductive film; 3: conductive particles; 10: laser lift-off device; 11: laser scanner; 12: mask; 13: projection lens; 20: anisotropic conductive film substrate; 21: substrate; 22: anisotropic conductive film; 23: removal portion; 30: anisotropic conductive film substrate; 31: substrate; 32: anisotropic conductive film; 33: removal portion; 34: single chip; 41: single chip with flash; 42: single chip with curling; 43: single chip with defect; 51: light shielding portion; 52: single chip; 53: light shielding portion; 54A to 54D: light shielding portion; 60: single chip film; 61: substrate; 62: anisotropic conductive film; 63: conductive particles; 64: monolithic; 64A: monolithic; 64B: monolithic; 70: wiring substrate; 71: substrate; 72: first electrode; 73: second electrode; 80: light-emitting element; 81: main body; 82: first conductive type electrode; 83: second conductive type electrode; 90: transfer substrate; 91: substrate; 101: quartz glass; 104: monolithic; 107: evaluation substrate; 107A: first comb electrode; 107B: second comb electrode; 108: μLED element; 108A: first electrode; 108B: second electrode; 109: PDMS sheet.
Claims
1. A method for manufacturing a monolithic membrane, wherein: An anisotropic conductive film provided on a substrate is irradiated with laser light from the substrate side, and the anisotropic conductive film at the irradiated portion is removed, thereby forming a single piece of a predetermined shape composed of the anisotropic conductive film on the substrate. The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
2. The method for manufacturing a single-piece film according to claim 1, wherein: 90% or more of the conductive particles in the anisotropic conductive film exist at an average value of center positions of the conductive particles in a thickness direction of the anisotropic conductive film.
3. The method for manufacturing a monolithic film according to claim 1, wherein: The laser beam is irradiated through a mask on which a light shielding portion having the predetermined shape is formed.
4. The method for manufacturing a monolithic film according to claim 1, wherein: The prescribed shape is at least one selected from a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle.
5. The method for manufacturing a monolithic film according to claim 1, wherein: The conductive particles in the anisotropic conductive film are orderly arranged in a surface direction.
6. The method for manufacturing a monolithic film according to claim 1, wherein: The anisotropic conductive film has a melt viscosity at 30° C. of 5,000 Pa·s or more and 500,000 Pa·s or less.
7. A monolithic membrane, wherein: have: A single piece of a predetermined shape composed of anisotropic conductive film, The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
8. The monolithic membrane according to claim 7, wherein: 90% or more of the conductive particles in the anisotropic conductive film exist at an average value of center positions of the conductive particles in a thickness direction of the anisotropic conductive film.
9. The monolithic membrane according to claim 7, wherein: The prescribed shape is at least one selected from a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle.
10. The monolithic membrane according to claim 7, wherein: The conductive particles in the anisotropic conductive film are orderly arranged in a surface direction.
11. The monolithic membrane according to claim 7, wherein: The anisotropic conductive film has a melt viscosity at 30° C. of 5,000 Pa·s or more and 500,000 Pa·s or less.
12. A method for manufacturing a display device, wherein: have: a forming step of irradiating the anisotropic conductive film provided on the substrate with laser light from the substrate side, removing the irradiated portion of the anisotropic conductive film, and forming a single piece of a predetermined shape composed of the anisotropic conductive film on the substrate; A transfer step of transferring the single piece of the specified shape to a specified position of a wiring substrate or an electrode surface of a light-emitting element; as well as A mounting step of mounting the light emitting element on the wiring substrate via the transferred single chip, The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
13. The method for manufacturing a display device according to claim 12, wherein: 90% or more of the conductive particles in the anisotropic conductive film exist at an average value of center positions of the conductive particles in a thickness direction of the anisotropic conductive film.
14. The method for manufacturing a display device according to claim 12, wherein: In the forming step, the laser beam is irradiated through a mask on which the light shielding portion having the predetermined shape is formed.
15. The method for manufacturing a display device according to claim 12, wherein: In the transfer step, laser light is irradiated from the substrate side to transfer the single piece of the predetermined shape to a predetermined position of a wiring board or an electrode surface of a light emitting element.
16. The method for manufacturing a display device according to claim 12, wherein: The prescribed shape is at least one selected from a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle.
17. The method for manufacturing a display device according to claim 12, wherein: The conductive particles in the anisotropic conductive film are orderly arranged in a surface direction.
18. The method for manufacturing a display device according to claim 12, wherein: The anisotropic conductive film has a melt viscosity at 30° C. of 5,000 Pa·s or more and 500,000 Pa·s or less.
19. A method for manufacturing a connection structure, wherein: have: a forming step of irradiating the anisotropic conductive film provided on the substrate with laser light from the substrate side, removing the irradiated portion of the anisotropic conductive film, and forming a single piece of a predetermined shape composed of the anisotropic conductive film on the substrate; a transfer step of transferring the single piece of the specified shape to a specified position of the first electronic component; as well as A mounting step of mounting a second electronic component on the wiring substrate via the transferred single sheet, The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
20. A display device, wherein: have: a plurality of light emitting elements; A wiring substrate for arranging light emitting elements; as well as curing the film to connect the plurality of light emitting elements to the wiring substrate, The cured film is formed by curing a single piece of a predetermined shape composed of an anisotropic conductive film. The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
21. The display device according to claim 20, wherein: 90% or more of the conductive particles in the anisotropic conductive film exist at an average value of center positions of the conductive particles in a thickness direction of the anisotropic conductive film.
22. The display device according to claim 20, wherein: The prescribed shape is at least one selected from a polygon formed by an obtuse angle, a rounded polygon, an ellipse, an oblong, and a circle.
23. The display device according to claim 20, wherein: The distance between the individual pieces is greater than 3 μm.
24. The display device according to claim 20, wherein: The light emitting elements are arranged in sub-pixel units constituting one pixel.
25. The display device according to claim 20, wherein: The individual chips are arranged on the wiring substrate in sub-pixel units or in pixel units.
26. A connection structure, wherein: have: a first electronic component; a second electronic component; and curing the film to connect the first electronic component to the second electronic component, The cured film is formed by curing a single piece of a predetermined shape composed of an anisotropic conductive film. The thickness of the anisotropic conductive film is not less than 0.9 times and not more than 8 times the particle diameter of the conductive particles in the anisotropic conductive film. The anisotropic conductive film has a melt viscosity at 30° C. of 2,000 Pa·s or more and 800,000 Pa·s or less.
Citation Information
Patent Citations
Transportation status management system
JP2022145317A
Display device using semiconductor light emitting device
US20150255505A1